Technical Potential of Evaporative Cooling in Danish and European Condition. (November 2015) - Pomianowski, Michal; Andersen, Christian Hede; Heiselberg, Per
Abstract: Evaporative cooling is a very interesting high temperature cooling solution that has potential to save energy comparing to refrigerant cooling systems and at the same time provide more cooling reliability than mechanical or natural ventilation system without cooling. Technical cooling potential of 5 different evaporative systems integrated in the ventilation system is investigated in this article. Annual analysis is conducted based on hourly weather data for 15 cities located in Denmark and 123 European cities. Investigated systems are direct, indirect, combinations of direct and indirect system and one with desiccant wheel. Obtained results indicate which system would be sufficient to provide necessary cooling load in order to maintain acceptable indoor temperature for specified range of heat gains and design air change rates.